Dermal T cell immunity and key regulatory signaling pathways: Implications in immune-mediated alopecia and hair regeneration - Nana Tao; Qingru Sun; Yuyuan Ying; Yitao Wang; Jianli Gao (Genes and Diseases)
Mammalian hair follicles undergo periodic regeneration, with recent research highlighting the immunological niche as a critical regulator of stem cell activity and hair follicle regeneration. Chemotactic signals from hair follicles attract macrophages and T cells, which, in turn, control the resting and differentiation of epithelial stem cells in both healthy and damaged conditions. T cells play a pivotal role in hair follicle regeneration, contributing to injury-induced hair neogenesis and physiologic hair cycling. However, disruption of this interaction can lead to clinically significant immune-mediated alopecia. Both scarring and non-scarring forms of alopecia arise from an imbalance in this dynamic system. In this review, we address the role of T cells in hair follicles, summarize related mechanisms, and highlight key genes involved in T cell differentiation and development. Our aim is to provide insights into the development of hair disorders linked to T cell immune homeostasis and hair follicle regeneration.